Impact of CONSORT extension for cluster randomised trials on quality of reporting and study methodology: review of random sample of 300 trials, 2000-8. (26th September 2011) - Ivers, N M; Taljaard, M; Dixon, S; Bennett, C; McRae, A; Taleban, J; Skea, Z; Brehaut, J C; Boruch, R F; Eccles, M P; Grimshaw, J M; Weijer, C; et al.
Abstract : Objective To assess the impact of the 2004 extension of the CONSORT guidelines on the reporting and methodological quality of cluster randomised trials. Design Methodological review of 300 randomly sampled cluster randomised trials. Two reviewers independently abstracted 14 criteria related to quality of reporting and four methodological criteria specific to cluster randomised trials. We compared manuscripts published before CONSORT (2000-4) with those published after CONSORT (2005-8). We also investigated differences by journal impact factor, type of journal, and trial setting. Data sources A validated Medline search strategy. Eligibility criteria for selecting studies Cluster randomised trials published in English language journals, 2000-8. Results There were significant improvements in five of 14 reporting criteria: identification as cluster randomised; justification for cluster randomisation; reporting whether outcome assessments were blind; reporting the number of clusters randomised; and reporting the number of clusters lost to follow-up. No significant improvements were found in adherence to methodological criteria. Trials conducted in clinical rather than non-clinical settings and studies published in medical journals with higher impact factor or general medical journals were more likely to adhere to recommended reporting and methodological criteria overall, but there was no evidence that improvements after publication of the CONSORT extension for cluster trials were more likely in trials conducted in clinical settings nor in trials published in either general medical journals or in higher impact factor journals. Conclusion The quality of reporting of cluster randomised trials improved in only a few aspects since the publication of the extension of CONSORT for cluster randomised trials, and no improvements at all were observed in essential methodological features. Overall, the adherence to reporting and methodological guidelines for cluster randomised trials remains suboptimal, and further efforts are needed to improve both reporting and methodology.